Kuhn dans la « révolution cognitive » - Arthur Massot (Revue d'anthropologie des connaissances)
The now well-known book of Thomas S. Kuhn, The Structure of scientific revolutions, was first published in 1962. In the field of American psychology, this book was widely quoted from the 1970s onwards, although not without debates. The aim of this paper is to highlight the historical and epistemological issues behind those debates. In particular, the proponents of the emerging cognitive psychology have used the Kuhnian theories to enforce their approach against behaviorism, which back then was dominant in American psychology. The rise of cognitivism has been supported by several characteristics of Kuhn's model: its internalist, discontinuous, monopolistic and universalist vision of science; the ambiguity of its formulations; the recognition of Kuhn by a wide audience during the 1970s; and the reiteration of the idea of a “cognitive revolution” that would have occurred in psychology.